2014
DOI: 10.7554/elife.01434
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis reveals self assembly and nanoscale segregation of two distinct cavin subcomplexes on caveolae

Abstract: In mammalian cells three closely related cavin proteins cooperate with the scaffolding protein caveolin to form membrane invaginations known as caveolae. Here we have developed a novel single-molecule fluorescence approach to directly observe interactions and stoichiometries in protein complexes from cell extracts and from in vitro synthesized components. We show that up to 50 cavins associate on a caveola. However, rather than forming a single coat complex containing the three cavin family members, single-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
164
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(182 citation statements)
references
References 37 publications
(38 reference statements)
6
164
1
2
Order By: Relevance
“…1A). Using pulldown experiments we found that cavin1 self-associated and bound to cavin2 and cavin3, as previously suggested (Gambin et al, 2014), but that cavin2 and cavin3 did not interact ( Fig. 1B; supplementary material Fig.…”
Section: Resultssupporting
confidence: 48%
“…1A). Using pulldown experiments we found that cavin1 self-associated and bound to cavin2 and cavin3, as previously suggested (Gambin et al, 2014), but that cavin2 and cavin3 did not interact ( Fig. 1B; supplementary material Fig.…”
Section: Resultssupporting
confidence: 48%
“…The cavins also have the ability to bind to PtdSer (16,17,20). Furthermore, a recent study demonstrated that there are 50 cavin1 molecules per caveola (15,21). Together these observations suggest that PtdSer may play a critical role in the formation and stabilization of caveolae.…”
Section: Edited By Dennis R Voelkermentioning
confidence: 66%
“…In the cellular context at first glance, the strength of the interaction between three cationic amino acids and the anionic phospholipid would be rather modest. However, as caveolae have been estimated to contain Ϸ144 Cav1 molecules (9,15), the number of basic residues per caveola is amplified to Ϸ432. Thus, the potential strength of the electrostatic interaction is considerable.…”
Section: Edited By Dennis R Voelkermentioning
confidence: 99%
“…24 This network of low affinity interactions presumably allows disassembly of caveolae in response to increased membrane tension as cavins are released from caveolae as they flatten. In addition, with an estimated 140-150 caveolin molecules 25 and 50 cavin1 molecules 26 in a single caveolae the lipid domain generated within caveolae may be quite distinct to that of the bulk plasma membrane. The biophysical properties of the caveolar domain generated by the combination of caveolin insertion into the membrane, the cytoplasmic coat of cavin proteins, and their distinct lipid composition might be very different to that of the bulk membrane but at present the precise quantitative parameters are unknown.…”
mentioning
confidence: 99%